The development of spatio-temporal data model for dynamic visualization of virtual geographical information system - Mohd. Rahim, Mohd. Shafry; Daman, Daut (Faculty of Computer Science and Information System, 2006)
Virtual Geographical Information Systems (VGIS) is known to be one of the technologies used to improve the presentation of geographic visualization. Developing an efficient spatiotemporal data model is very important in contributing to the functionality improvement of the VGIS. Thus in this research, we focused on the data management aspect and has developed a suitable spatiotemporal data model for storing and retrieving volumetric geographic movement information. Volumetric is one type of spatial object in the VGIS, which is used to visualize 3D information. In order to develop real processes in VGIS, we have integrated the time element as an important factor to 3D objects. Time has been integrated with the data model, and temporal versions of volumetric surface data can be stored by using the model. This research also uses linear interpolating model techniques to visualize the movement changes. This application was implemented by developing a prototype visualization system using a Triangulation Irregular Network (TIN) with integrated time in the TIN structure. Result shows that the proposed data model is able to perform well with a visualization algorithm using linear interpolation and an improved TIN structure. This research contributed a suitable Spatiotemporal Data Model for managing continuous volume and 3D geographic movement data in VGIS and also a prototype of Spatiotemporal Database System which is can be implemented in GIS software. This can be particularly useful in applications such as geographic historical management data application, morphology of the terrain data, mobile movement, and Global Positioning System (GPS) application.